2019
DOI: 10.1096/fj.201802117r
|View full text |Cite
|
Sign up to set email alerts
|

A role for phosphatidylcholine and phosphatidylethanolamine in hepatic insulin signaling

Abstract: Phosphatidylethanolamine N‐methyltransferase (PEMT) is an important enzyme in hepatic phosphatidylcholine (PC) biosynthesis. Pemt−/− mice fed a high‐fat diet are protected from obesity and whole‐body insulin resistance. However, Pemt−/− mice develop severe nonalcoholic steatohepatitis (NASH). Because NASH is often associated with hepatic insulin resistance, we investigated whether the increased insulin sensitivity in Pemt−/− mice was restricted to nonhepatic tissues or whether the liver was also insulin sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…2C, D and 3D, E) independent of adiposity. In agreement, we have recently demonstrated that insulin signaling is improved in primary hepatocytes and hepatoma cells that lack PEMT, which was linked to a decrease in the PC:PE molar ratio or an increase in PE (9).…”
Section: Pemt Deficiency Promotes Insulin Sensitivity Independent Of supporting
confidence: 85%
See 1 more Smart Citation
“…2C, D and 3D, E) independent of adiposity. In agreement, we have recently demonstrated that insulin signaling is improved in primary hepatocytes and hepatoma cells that lack PEMT, which was linked to a decrease in the PC:PE molar ratio or an increase in PE (9).…”
Section: Pemt Deficiency Promotes Insulin Sensitivity Independent Of supporting
confidence: 85%
“…Lack of PEMT reduces the hepatic PC:PE molar ratio, impairing membrane integrity and leading to endoplasmic reticulum (ER) stress and liver disease (3,4,(6)(7)(8). Interestingly, the reduction in the hepatic PC:PE molar ratio is also associated with an improvement in hepatic insulin sensitivity in primary hepatocytes of Pemt 2/2 mice, suggesting that the protection against IR is independent of obesity and the development of NAFLD (9).…”
mentioning
confidence: 99%
“…Consistent with our findings, several studies have also reported elevated lysine and PE levels in T2DM patients with glucose intolerance, insulin resistance and obesity . Increased plasma stearic acid, which could promote insulin resistance, inflammation, and obesity, is a potential predictor of diabetes in obesity .…”
Section: Discussionsupporting
confidence: 92%
“…(36) Importantly, it has been described that treatments to reduce the PC-to-PE ratio in the liver protect against the development of hepatic insulin resistance. (37) LysoPC is a death effector in the lipoapoptosis of hepatocytes. (38) In NASH, the diacylglycerol (DAG) that is normally consumed to produce PEs by the CDP-ethanolamine pathway is instead converted to TGs, promoting LD formation.…”
Section: Discussionmentioning
confidence: 99%